Hepatic Encephalopathy following Transjugular Intrahepatic Portosystemic Shunt Placement - Thornburg, Bartley (Seminars in Interventional Radiology, 2023)
Hepatic encephalopathy (HE) is a complex condition that arises as a complication of chronic liver disease and portosystemic shunting. Its pathophysiology involves several factors, including impaired ammonia metabolism, portosystemic shunting, sarcopenia, and systemic inflammation. The symptoms of HE can vary significantly, with manifestations ranging from subclinical signs to a comatose state. The West Haven classification system is most commonly used to grade the severity of HE. There is a broad differential for the presenting symptomatology of HE and other causes of altered mental status must be excluded during the workup. HE is a well-known complication of transjugular intrahepatic portosystemic shunt (TIPS) placement. Even though newer stent designs help reduce the risk of HE with smaller diameter shunts, it is essential that patients are counseled regarding this potential risk prior to the procedure. Once a diagnosis of HE has been confirmed, the mainstay of therapy is lactulose and rifaximin. In cases where a patient has received a TIPS placement and continues to experience refractory HE despite medical therapy, it may be necessary to consider shunt reduction or closure.
Keywords: TIPS; hepatic encephalopathy; cirrhosis